2015
DOI: 10.1016/j.ijmyco.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with treatment success and death in cases with multidrug-resistant tuberculosis in Bulgaria, 2009–2010

Abstract: Most MDR-TB patients in this first treatment cohort using WHO-recommended norms had advanced disease explaining the high mortality and low success. Early, adequate treatment of MDR-TB patients can improve outcomes and avert transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 8 publications
1
11
2
1
Order By: Relevance
“…Over 17% of study participants had unfavourable treatment outcomes (5% mortality and 12% lost-to-follow-up), similar to that reported by Meressa et al [44],. However, this is lower than that reported by Dheda et al, [46] and Milanov et al, [47] in South Africa and Bulgaria who both documented over 50% unfavourable treatment outcomes. Previous findings have argued that severe malnutrition (BMI < 16 kg/m2), HIV coinfection, previous history of anti-TB therapy and drug adverse events can predict poor treatment outcomes [47,48].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Over 17% of study participants had unfavourable treatment outcomes (5% mortality and 12% lost-to-follow-up), similar to that reported by Meressa et al [44],. However, this is lower than that reported by Dheda et al, [46] and Milanov et al, [47] in South Africa and Bulgaria who both documented over 50% unfavourable treatment outcomes. Previous findings have argued that severe malnutrition (BMI < 16 kg/m2), HIV coinfection, previous history of anti-TB therapy and drug adverse events can predict poor treatment outcomes [47,48].…”
Section: Discussioncontrasting
confidence: 58%
“…However, this is lower than that reported by Dheda et al, [46] and Milanov et al, [47] in South Africa and Bulgaria who both documented over 50% unfavourable treatment outcomes. Previous findings have argued that severe malnutrition (BMI < 16 kg/m2), HIV coinfection, previous history of anti-TB therapy and drug adverse events can predict poor treatment outcomes [47,48]. In this study, 29.9% of the study participants had low BMI and 23% were infected with HIV but had no effects on MDR-TB treatment outcomes.…”
Section: Discussioncontrasting
confidence: 58%
“…A study in Lithuania reported that smear-positivity at diagnosis was associated with about 1.5 times increase in the risk of death among MDR-TB patients [16]. Furthermore, smear positivity at diagnosis was also associated with a five-fold increase in the risk of death among MDR-TB patients in a recent study in Bulgaria [17]. The influence of smear positivity at diagnosis on the survival of MDR-TB patients reported in this study is consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 95%
“…Hasil penelitian ini tedapat perbedaan dengan hasil penelitian sebelumnya yang menunjukkan adanya hubungan signifikan antara jenis kelamin dan hasil pengobatan. 10,11 Perbedaan hasil penelitian ini dengan penelitian sebelumnya bisa terjadi karena adanya perbedaan metode penelitian yang digunakan, jumlah sampel yang digunakan, lokasi penelitian, dan karakteristik sampel. Hubungan antara jenis kelamin dan hasil pengobatan sulit untuk dinilai karena bersifat k ompleks.…”
Section: Factors Associated With Recovery Success After Short Treatmeunclassified